ІВАН ОГІЄНКО - ПРОВІДНА ПОСТАТЬ УКРАЇНСЬКОГО МОВОЗНАВСТВА, КУЛЬТУРИ ТА ІСТОРІЇ ЦЕРКВИ - ЗОРИК, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У даній статі розглянуто творчу, наукову та громадську діяльність видатногонауковця, професора Іван Огієнка, «людини праці і обов’язку», «невтомного працівникаукраїнського Ренесансу», «ініціатора розвою української культури», філософа й педагога,як його називали сучасники-бібліографи, захоплені його фантастичною працьовитістю.Іван Огієнко був блискучим популяризатором, натхненним пропагандистом культуриукраїнської мови, літератури, краєзнавства, славістики, філософії, народноїархітектури, освіти, бібліографії в ХХ столітті.Зорик В.А. ИВАН ОГИЕНКО – КЛЮЧЕВАЯ ФИГУРА УКРАИНСКОГОЯЗЫКОВЕДЕНИЯ, КУЛЬТУРЫ И ИСТОРИИ ЦЕРКВИ В данной статье рассмотренатворческая, научная и общественная деятельность выдающегося ученого, профессораИвана Огиенкo, «человека труда и обязательств», «неутомимого работника украинскогоРенессанса, «инициатора рассвета украинской культуры», философа и педагога, как егоназывали современники-библиографы восхищенные его фантастическим трудолюбием.Иван Огиенко был блестящим популяризатором и пропагандистом культуры украинскогоязыка, литературы,краеведения, славистики, философии, народнойархитектуры,просвещения, библиографии в ХХ столетии.Ключевые слова: украинский Ренессанс,спектр.славистика,библиография,приват-доцент,популяризатор,учитель.Zorik V. IVAN OGIENKO- BRIGHT REPRESENTATIVE OF THE UKRAINIAN,CULTURE AND THE HISTORY OF CHURCH This article examines the creative, scientificand public activity of outstanding scientist, professor Ivan Ogienko, “the person of labor andobligations”, “untiring worker of Ukrainian Renaissanse”, “the initiator of the dawn ofUkrainian culture”, philosopher and teacher, as him called contemporaries bibliographersenraptured by his fantastic diligence. Ivan Ogienko was the bright popularizer and thepropagandist of the culture of Ukrainian language, literature, regional study, Slav philology,philosophy, folk architecture, education, bibliography in 20th century. The author gives thedetailed characteristic of the fundamental periods of the life of scientist,were analyzed thereasons, which influenced the Ogienko’s decision to leave beloved Ukraine.Biography of thispatriot and devotee reflected dramatic changes in the political history of the Ukraine inTwentieth century, but it is the model of adherence to one’s duty and to the cause of nationalscience. At the same time Ogienko’s activity pushed and stretched national boundaries andserved strengthening the idea of the world value of Ukrainian culture, emphasized the Europeannature of the nation and contributed to worldwide popularization of all the best that theUkrainian people acquired within the millenia of the cultural and political development.Keywords: Ukrainian renaissance, spectrum ,slavistiks, bibliography, assistant professor,popularizer, teacher.